Silicon in Agriculture 2015
DOI: 10.1007/978-94-017-9978-2_11
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Silicon on Crop Growth, Yield and Quality

Abstract: Silicon (Si) has widely been reported to increase the growth and biomass, yield and quality of a broad range of crops including monocotyledonous crops such as rice, wheat, maize, barley, millet, sorghum and sugarcane that actively take up and accumulate high amounts of Si in their organs and some dicotyledonous crops such as cotton and some vegetable and fruit crops. The yield increment, however, may be attributable not only to the benefi cial effects of Si including growth promotion, lodging resistance and bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 52 publications
2
31
0
8
Order By: Relevance
“…Studies of silicon application to the soil conducted in north-east China in the years 2005–2006 indicated an increase in corn yield by 5.6–10.4% (on average by 7.7%) in comparison with the control variant [ 32 ].…”
Section: Cerealsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of silicon application to the soil conducted in north-east China in the years 2005–2006 indicated an increase in corn yield by 5.6–10.4% (on average by 7.7%) in comparison with the control variant [ 32 ].…”
Section: Cerealsmentioning
confidence: 99%
“…Studies with application of silicon to the soil conducted in China in the years 2005–2006 showed an increase in tomato yield by 8.7–15.9% (on average by 12.0%) compared with the control treatment [ 32 ]. The studies on tomato were conducted in Brazil with three silicon fertilizers (calcium silicate, potassium silicate, and sodium silicate) in five doses (0, 100, 200, 400, and 800 kg SiO 2 ∙ha −1 ) [ 53 ].…”
Section: Berry Crops and Vegetablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Costa et al (2016) also observed that Si concentrations of 0.28 and 0.55 g pot −1 (pots contained 1100 g of tropstrato(r) substrate) yielded the highest stem dry weight of 1.32 and 1.38 g respectively, in passion fruit, compared to 0.81 g of dry weight in the control treatment. Liang et al, (2015) also observed that the effects of Si on plant growth are often complemented by other factors such as pH adjustment and the acquisition of macro/micro nutrients contained in silicate fertilizers. In our study, the addition of SiBC raised the soil pH from 6.83 ± 0.4 in unmodified soil to 8.01 ± 0.1 in SiBC + soil (Table 2) which may have also influence biomass production.…”
Section: Effects Of Silicon Biochar On Biomass Yield In Spinach Plantmentioning
confidence: 99%
“…It is the second most abundant element after oxygen [ 1 , 2 ] in soil. Since silicon is an essential element and a plant nutrient [ 3 , 4 ], it has an important role in plant growth, yield [ 3 , 5 , 6 ], photosynthetic properties, chlorophyll contents, and enzyme activity [ 7 9 ], especially under stressful conditions [ 1 , 10 ]. Currently, there is no evidence showing the direct role of silicon in plant metabolism.…”
Section: Introductionmentioning
confidence: 99%